A Diiron Hydrogenase Mimic Featuring a 1,2,3-Triazolylidene - Andrea Mele (CHIMIA, 2020)
A novel complex featuring a mesoionic carbene [Fe2(CO)5(trz)(μ-pdt)] (1) (trz = 1-phenyl-l,3-methyl,4-butyl-1,2,3-triazol-5-ylidene), was synthesized and spectroscopically and structurally characterized. The reductive behaviour of this compound in the presence and in the absence of acid (CH3CO2H) was examined by cyclic voltammetry (CV) that revealed the lack of efficient activity towards proton reduction.